Orquestração de vozes na carta aos Hebreus: Um discurso marcado pela expressão de gênero encômio em Hb 1.1-2.4. - Arruda, Edivaldo Ferreira de (2022)
The Letter to the Hebrews is a New Testament book that contains multiple allusions to texts from different Old Testament contexts. As a framer, the author assumes an axiological position through which he assesses the reality of his world from other discourses related to the practices of the Judeo-Hellenic traditions. Through a set of interactions in dialogic syncrises, not merely a treatise on common life is composed, but a scenario of the latest “visions”. Under a genre profile in the confession, The Letter to the Hebrews brings together a diversity of genres through which the author materializes a sermon centered on the responsive action of his audience, in the light of a high-level representational language of classical oratory. In the light of the analysis of introductory genres, we aim to elucidate the problems related to antagonistic generic aspects placed side by side, namely: the expression of the praise of a “great encomium” mixed with gardening elements of the paraenetic genres, at various levels of speech representation other. This meaning is anchored in the promotional function of the excerpt Hb 1.1-2.4, coined by us as “factual encomium”, and taken as corpus for evidencing generic expressions resonant in the concrete utterance. Therefore, the intertextual dimension constitutes a contribution to the investigation of language phenomena in the variety of voices evoked in the text. The theoretical framework encompasses the principles of the theory of introductory genres in Bhatia (2004) and Bezerra (2006; 2017) combined with dialogicity/ heterogeneity in Bakhtin (2015a; 2015c; 2016), Volochinov (2017; 2019) and Authier-Revuz (2004; 2020). Based on a qualitative method, we reflect on the rhetorical strategies of communication of the Christian faith, focusing on empirical research based on bibliographic corpora analyses. In short, this study strives for the functionality of the triad: text, discourse and context in terms of communicative purpose. We hope to reconcile the common elements of discursive communication of dialogic discourse analysis and textual linguistics. Therefore, the research is guided by the discursive genres present in the writing that fit the representation of speech, bringing to light the appreciation of the structure of thought for future studies, without losing sight of the extraverbal aspects identified in the most diverse studies on The Letter to the Hebrews.